Overview: Incomes and inequality in China, 2007-2013 - Chuliang Luo; Terry Sicular; Shi Li (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
In this chapter we examine trends in China's household incomes, income distribution and inequality for China as a whole and for each of the urban, rural and rural-urban migrant subgroups, as well as analyzing changes in the income gaps between the urban and rural sectors and among the Eastern/Central/Western regions using the CHIP 2007 and 2013 data. Our base estimates show a decline in national inequality from 2007 to 2013. This decline is robust to alternative income definitions and different inequality indexes. The decline reflects reductions in important dimensions of inequality including the rural-urban income gap, regional income gaps, and inequality in the distribution of the major components of household income, e.g. wage earnings, asset income, etc. The decline in national inequality would have been even larger if not for rising inequality within the urban and rural sectors and the growing importance of unequally distributed income components, such as income from assets and imputed rents on owner-occupied housing. Moreover, the decline in national inequality is not robust to adjustments to correct for spatial differences in the cost of living and for under-representation of top-income groups in the survey sample. These adjustments reveal that some, if not all, of the apparent reduction in inequality from 2007 to 2013 is due to changes in prices and the growing importance of top-income individuals and their incomes that are not captured in the household surveys. The chapter contains further, detailed analyses of changes in incomes and income distribution within each of the urban, rural and migrant population subgroups.
Keywords: D31; O15; O53; P25; P36; 330; China; inequality; income distribution